Evaluating the aesthetics of endgame studies: A computational model of human aesthetic perception - Iqbal A. (2023)
In this paper, we explain how an existing computational aesthetics model for three-move mate problems was improved and adapted to suit the domain of chess endgame studies. Studies are typically longer and more sophisticated in terms of their perceived aesthetics or beauty. They are therefore likely a better test of the capability of machines to evaluate beauty in the game. Based on current validation methods for an aesthetics model such as this, the experimental results confirm that the adaptation was successful. In the first experiment, the new model enabled a computer program to distinguish correctly between composed studies and positions with sequences resembling studies taken from real games. In the second, the computational aesthetic evaluations were shown to correlate positively and well with human expert aesthetic assessment. The new model encompasses the previous three-mover one and can be used to evaluate beauty as perceived by humans in both domains. This technology pushes the boundaries of computational chess and can be of benefit to human players, composers, and judges. To some extent, it may also contribute to our understanding of the psychology of human aesthetic perception and the mechanics of human creativity in composing problems and studies. 2009-2012 IEEE.